Creep subsidence prediction algorithm considering the effect of stress history for subgrades - Huang, Jian; Lu, Xusheng; Hu, Hexiang (Frontiers in Materials, 2023)
In this study, the power function model was modified to explain the creep strain of coarse-grain and fine-grain soils in a uniform manner. And then, two creep subsidence prediction algorithms considering stress history and without considering stress history were proposed based on the modified power function model and Bjerrum’s reclassification of consolidation. The two proposed algorithms were in comparison with two widely used subsidence prediction algorithms in practical engineering based on field subsidence observation data from the subgrade of Haolebaoji-Ji’an Railway. According to the comparison results, the prediction algorithm considering stress history provides a more precise and reliable prediction over two conventional algorithms with a limited amount of available observation data. However, the prediction algorithm without considering stress history have poor prediction results.